La Prise En Charge Des Detenus Infectes Par Le Vih/Sida A La Maison D’arret Et Correction D’abidjan (Maca) - Ahissan, Alexandre Kouassi (European Scientific Journal, ESJ, 2017)
This article shows the effects of different forms of care on the living conditions of prisoners infected with HIV / AIDS. From a methodological point of view, the study used three instruments: direct observation, individual free interview and documentary research. As for the method of data analysis, content analysis and qualitative analysis were used to better understand the content of the respondents' speeches. This study presents the various forms of care provided to prisoners living with HIV / AIDS, which begin with awareness-raising and voluntary testing. And these care are often contributed by their living conditions.